Self‐reassurance moderated by identity dysfunction: Associations with distress and impairment. (25th November 2021) - Kealy, David; Ben‐David, Shelly; Spidel, Alicia; Wadsley‐Rose, Saffron; Kim, Dan
Abstract: Although compassionate and reassuring self‐responding has been consistently linked with wellbeing, the involvement of identity dysfunction in this association is unclear. This study examined the interaction of self‐reassurance and identity dysfunction in relation to severity of psychological distress and social impairment among 243 clients attending mental health clinics. Participants completed measures of self‐reassurance, identity dysfunction, psychological distress, and social functioning; correlation and regression analyses were used to examine associations and interaction effects. The interaction between self‐reassurance and identity dysfunction was significant in relation to both distress and impairment, with the negative association between self‐reassurance and distress and impairment stronger as identity dysfunction diminished from high to moderate and to low levels of severity. Thus, higher self‐reassurance was most strongly associated with lower distress and impairment among clients with relatively stable identity, indicating the importance of considering identity dysfunction in counseling to enhance clients' compassionate and reassuring self‐responses.